The Role of Communication Competence in Buffering Against the Negative Effects of Alcohol-Related Social Networking Site Usage. (1st September 2016) - Thompson, Charee M.; Romo, Lynsey K.
Abstract : College students' alcohol-related social networking site (SNS) usage is associated with alcohol problems; however, individual factors that increase this risk are less understood. We posit the degree to which students experience alcohol problems related to their SNS usage hinges upon how skillfully they manage their communication on SNS. As such, we focus on how SNS competence predicts students' SNS usage and subsequent alcohol problems. We analyzed data collected from 364 undergraduate students and found support for SNS competence serving a moderating role between alcohol-related SNS behavior and alcohol problems. SNS competence—appropriateness in particular—buffers against the negative effects of alcohol-related SNS use. Our research offers several theoretical implications and practical applications for social media literacy-based drinking interventions.